ACTUAL-IDEAL SELF DISCREPANCY DALAM PERILAKU PENGAMBILAN KEPUTUSAN - Nanang Erma Gunawan (Paradigma, 2010)
Everyday, we faced with many choices have to be chosen in order to reach our goals. This may not only for present time, but also our past which is leading to our recent conditions. Many of our choices are not leading to our real goals, because of some external determinants we could not control or ignored. Sometimes it causes disequilibrium toward our psychological condition, familiarly called actual-ideal self-discrepancy. This article would discus about that phenomena and an example research have been done as a similarcase of that term. Decision making context have been a focus of the case track and thus some asymmetrical choices are presented as a reference toward the daily same cases we found.Keywords : Actual-Ideal Self Discrepancy, Decision Making, MeansEnd Chains